Thermoelectric Performance of Doped Polyaniline from Textile Dye Waste - Eka Cahya Muliawati; Herma Syafika (CV. Get Press Indonesia, 2026)
This study investigates the thermoelectric performance of polyaniline (PANI) doped with textile dye waste, specifically methyl orange (MO) and congo red (CR), as sustainable alternative dopants. Polyaniline was synthesized via oxidative polymerization using ammonium persulfate as the oxidant at varying dopant concentrations (0.1–1.0 M), with three independent replicates per condition to ensure statistical validity. Characterization was performed using FTIR spectroscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM), and four-probe electrical conductivity measurements. Thermoelectric performance was evaluated through the Seebeck coefficient (S), power factor (PF = S²σ), and figure of merit (ZT). Results show that PANI-CR 0.5 M yielded the highest Seebeck coefficient of 42.7 µV/K, electrical conductivity of 127.3 S/cm, and power factor of 2.31 × 10⁻⁴ W/m·K². The ZT value obtained reached 0.434 at the optimal temperature of 340 K, a significant improvement of 340% compared to undoped PANI, substantially superior to PANI-HCl (ZT = 0.040) and competitive with organic thermoelectric materials reported in recent literature (e.g., PANI-CSA: 1.83 × 10⁻⁴ W/m·K² at 300 K). Unlike conventional approaches using synthetic dopants, this waste-to-material strategy demonstrates that textile dye waste can be valorized as functional dopants, offering dual environmental benefits: reducing water pollution (0.01–1 mg/L threshold) while producing low-cost organic thermoelectric materials. These findings highlight the potential for scaling to industrial thermoelectric devices and battery thermal management systems. Future work will explore composite materials with carbon nanostructures and optimization through polymerization condition engineering.